Pengaruh Edukasi, Entertain, Eskapisme, dan Estetika pada Pelajar dan Mahasiswa sebagai Determinan Re-Intensi Kunjungan di Desa Wisata Nglanggeran - Prakosa, Adhi; Jasmin Nur Arroyani, Yulia; Sudaryana, Arif (Indo-MathEdu Intellectuals Journal, 2024)
The type of educational tourism is a tourism village. This research focuses on analyzing the behavioral intentions of students and college students in tourism villages. This study aims to test the Experience Economy Model, namely the experience of education, entertainment, escapism, and esthetics on tourists' intention to revisit to the Nglanggeran Tourism Village, Yogyakarta. This research is a quantitative study with a total of 200 respondents and the sampling technique used a purposive sampling technique. The data collection technique was carried out by distributing questionnaires. The data analysis technique used is multiple linear regression analysis using the SPSS 23. The results of this study indicate that Education, Entertainment, Escapism, and Esthetics has a positive and significant effect on the intention to revisit to Nglanggeran Tourism Village